Simulation of reactive distillation column for n-butyl acrylate production from dilute acrylic acid - Jesslyn, Tan Kim Ean (2014)
The recovery of dilute acrylic acid from the wastewater stream during the production of acrylic esters in the industries has gained a significant amount of attention due to its economic and environment issues. The amounts of acrylic acid which are usually found to contain in the wastewater stream range from 4-10 % w/w. The most frequent used method to treat wastewater containing acrylic acid is by incineration which is neither economically feasible nor environment friendly. One of the promising methods is recovery of acrylic acid from wastewater through esterification. Acrylic acid could be converted to acrylic ester while wastewater could be purified. To date, study about esterification by using diluted acrylic acid has not been reported in the literature. In this present work, a simulation study on the direct utilization of dilute acrylic acid in the production of n-butyl acrylate via esterification with n-butanol in a reactive distillation column was presented. The reaction is heterogeneously catalyzed by ion exchanged resin (Amberlyst-46). A pseudo-homogeneous kinetic model was used to describe the reaction kinetics. An equilibrium stage model was applied and the proposed model was validated with experimental data from past research study. The validated model was then used to study effect of various parameters like acrylic acid concentration, catalyst loading, reboiler duty, reflux ratio, number of trays in reactive section and number of trays in separation section. From this study, it can be seen that the best operating conditions in recovering 4% w/w acrylic acid from the wastewater stream were with a catalyst loading of 0.105 kg/m, reboiler duty of 283.133 kJ/hr, reflux ratio of 1.0 and finally with 7 trays in the reactive section and 2 trays in the rectifying and stripping section respectively. With these operating conditions, 95.245 % of AA managed to be converted into BA. The findings have proven the feasibility of the acrylic acid recovery via esterification in reactive distillation column and it serves as the groundwork for the detailed column design and experimental study in the future